Vein Patch Closure Using Below the Knee Greater Saphenous Vein for Femoral Endarterectomy Procedures is Not Always a Safe Choice. (2017) - Berner, M.; Lattmann, Th.; Stalder, Ph.; Wigger, P.
Abstract : Background: The complication of vein patch rupture is well described after carotid patch angioplasty; however, there is a paucity of data about the safety of vein patch closure in the setting of femoral endarterectomy. Methods/results: From May 2012 to May 2015, 115 femoral endarterectomies with patch closure were performed. A patch rupture occurred in three cases (2.6%) with a mortality rate of 66% (2/3). In all cases the greater saphenous vein below the knee was used as patch material. Discussion/conclusion: Vein patches, particularly from small calibre veins, should be excluded in femoral endarterectomy procedures as they pose a substantial risk of rupture. Highlights: Choice of patch material for endarterectomy procedures of the common femoral artery may be crucial. Patch rupture after use of the greater saphenous vein occurs in 3% of cases. A particular risk of rupture occurs after the use of below knee greater saphenous vein patches. Patch rupture is associated with a high mortality rate.